A New Approach to Estimating the Production Function for Housing - Epple, Dennis; Gordon, Brett; Sieg, Holger (American Economic Review, 2010)
Dating to the classic works of Alonso, Mills, and Muth, the production function for housing has played a central role in urban economics and local public finance. This paper provides a new flexible approach for estimating the housing production function which treats housing quantities and prices as latent variables. The empirical analysis is based on a comprehensive database of recently built properties in Allegheny County, Pennsylvania. We find that the new method proposed in this paper works well in the application and provides reasonable estimates for the underlying production function. (JEL C51, D24, R11, R31)